2019
DOI: 10.1021/acs.bioconjchem.9b00482
|View full text |Cite
|
Sign up to set email alerts
|

Squaraine Dyes: Molecular Design for Different Applications and Remaining Challenges

Abstract: Squaraine dyes are a class of organic dyes with strong and narrow absorption bands in the near-infrared. Despite high molar absorptivities and fluorescence quantum yields, these dyes have been less explored than other dye scaffolds due to their susceptibility to nucleophilic attack. Recent strategies in probe design including encapsulation, conjugation to biomolecules, and new synthetic modifications have seen squaraine dyes emerging into the forefront of biomedical imaging and other applications. Herein, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
127
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 105 publications
0
127
0
Order By: Relevance
“…The advancement of organic opto‐electronics relies on the development of robust organic semiconductors suitable for processing into functional thin films. Anilino squaraines are quadrupolar, donor‐acceptor‐donor‐type small molecule semiconductors that are easily accessible via condensations reactions . In the solid, they are characterized by strong intermolecular interactions mediating intense excitonic coupling with visible light, which renders them well suited for light harvesting and detection applications .…”
Section: Introductionmentioning
confidence: 99%
“…The advancement of organic opto‐electronics relies on the development of robust organic semiconductors suitable for processing into functional thin films. Anilino squaraines are quadrupolar, donor‐acceptor‐donor‐type small molecule semiconductors that are easily accessible via condensations reactions . In the solid, they are characterized by strong intermolecular interactions mediating intense excitonic coupling with visible light, which renders them well suited for light harvesting and detection applications .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] As an essential material for FL imaging, organic functional dyes play a very significant role in providing a visual fluorescence signal. [ 2 ] Fluorescent agents with emission in the first near‐infrared (NIR‐I) window have presented many advantages in lowering tissue scattering, minimizing autofluorescence, improving tissue penetration, and promoting signal‐noise ratio. They have been widely applied in the detection of bioactive species, labeling of proteins and cells, diagnosis and treatment of diseases, etc.…”
Section: Introductionmentioning
confidence: 99%
“…An example of an NIR dye is IR800CW (39), which is currently in phase II trials for fluorescence imaging and has shown optoacoustic signal generation with associated imaging targets (40). Recently, the potential for the use of squaraine dyes in optoacoustic applications has been summarized, with the summary including how structural characteristics are thought to affect absorption spectra (41). Synthesized organic dyes are most often used for perfusion imaging when used as single-element contrast agents, but incorporation into other technologies provides improvements to photostability, clearance, and specificity by active targeting for use as a molecular probe (42).…”
Section: Exogenous Agentsmentioning
confidence: 99%